Changing practice in physical restraint - Anton Smith; Tanya Ulmer (Scottish Journal of Residential Child Care, 2009)
Oak Hill Boys Ranch was established in 1961 in Alberta, Canada. It serves as a highly comprehensive residential treatment center for 11- 16 year old male youth. Young persons who are referred to Oak Hill Boys Ranch require residential treatment services for problems associated with trauma related to neglect and/or physical, emotional and sexual abuse.